Artificial regeneration with Quercus ilex L. and Quercus suber L. by direct seeding and planting in southern Spain - González-Rodríguez, Victoria; Navarro-Cerrillo, Rafael M.; Villar, Rafael (Annals of Forest Science, 2011)
& Introduction The limited ability of Quercus species to regenerate naturally in Mediterranean forests has led to the development of various artificial regeneration methods; however, there is no general consensus as to what specific method is the best one for this purpose. & Material and methods In this work, we assessed morphology, growth and survival of two Quercus species (Quercus ilex ssp. ballota and Quercus suber) using two different methods of artificial regeneration (viz. direct seeding and planting) and two seedling ages (1-year-old seedlings and 3-year-old seedlings) in southern Spain. & Results and discussion The 1-year-old seedlings of both species were found to exhibit the highest survival percentages and direct-seeded plants intermediate survival values. For direct-seeded plants, seed mass was found to have a significantly positive effect on the establishment success in both species. No clear-cut trend in survival was detected in the 3- year-old seedlings. The survival of the 3-year-old Q. suber seedlings and the direct-seeded plants was similar, but not in Q. ilex, where the survival of the 3-year-old seedlings was the lowest. The latter result may have been a consequence of cultivation in smaller containers leading to root deformation and limiting plant access to water. Differences in survival could not be ascribed to morphological and growth variables or stomatal conductance. & Conclusion Based on the results, all three artificial regeneration methods can be similarly effective provided appropriate nursery cultivation conditions are used and seeds are protected against predators, the best choice in each case being dictated by the particular restoration goals.
Keywords: artificial regeneration; Nursery; oak; Seedling; sowing

Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings - Domínguez Núñez, José Alfonso; Planelles González, Rosa; Rodríguez Barreal, José Antonio; Saiz de Omeñaca González, José Antonio (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.
Keywords: á mineral nutrition á; black truffle á drought; Black trufﬂe; Drought hardening; Elastic adjustment; elastic adjustment á inoculation; hardening á; Inoculation; Mineral nutrition; Nursery; nursery á osmotic adjustment; osmotic adjustment

Influence of water-stress acclimation and Tuber melanosporum mycorrhization on Quercus ilex seedlings - Domínguez Núñez, José Alfonso; Planelles González, Rosa; Rodríguez Barreal, José Antonio; Saiz de Omeñaca González, José Antonio (Agroforestry Systems, 2008)
Mycorrhizal and non-mycorrhizal holm oak (Quercus ilex L.) seedlings inoculated with black trufﬂe (Tuber melanosporum) were grown under nursery conditions and subjected to drought hardening for 4 months in autumn and winter followed by irrigation for 10 days. Leaf water potential and stomatal conductance were monitored during the 4 months of drought. When the test was completed (March), measurements were made for each treatment (inoculated or non-inoculated), and watering regime (watered and water-stressed). Pressure–volume curves, osmotic potential at full turgor, osmotic potential at zero turgor and the tissue modulus of elasticity near full turgor were calculated. Mycorrhizal colonization and growth, and the content of the main mineral nutrients N, P, K, Ca and Mg were measured. Water stress affected plant growth, caused an elastic adjustment of the plant tissues, and decreased the P and K content, and inoculation improved the nitrogen content. Drought acclimation apparently achieved the goal of improving the drought tolerance of holm oak seedlings, without depressing ectomycorrhizal root colonization by T. melanosporum.
Keywords: á mineral nutrition á; black truffle á drought; Black trufﬂe; Drought hardening; Elastic adjustment; elastic adjustment á inoculation; hardening á; Inoculation; Mineral nutrition; Nursery; nursery á osmotic adjustment; osmotic adjustment

EFECTO DE DISTINTOS TIPOS DE ENVASE, SUSTRATO y GRADOS DE ENDURECIMIENTO EN LA PRODUCCIÓN DE PLANTA DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM. - SUÁREZ, Ma ANGELES; ÁZQUEZ, FRANCISCO V; Baselga, Pilar (II Congreso Forestal Español, 1997)
Different treatments about olm oak (Quercus rotundifolia Lam.) and cork oak (Quercus suber L.) plants' production are comparied. It has been worked with two kinds of containers, three kinds of substratums and two degrees of plants' protection during the cultivation
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus

EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. - Suarez, M Ángeles; VÁzquez, Francisco; Baselga, Pilar; Torres, Enrique; CUEVAS, SERAFÍN (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus; Reforestation

Efeitos da poda radicular na produçáo de plantas de sobreiro em viveiro (quercus suber l.) - Santos, Maria de Lourdes; PAULINO, ISABEL MARGARIDA ORFÁO (II Congreso Forestal Español, 1997)
The work was accomplished in the Seed Laboratory of National Forestry Station. The aim is to observe, in the nursery plants production, the pruning root effects made at several levels. The seeds provenance are the selected trees. The results permitted to conclude that: • The plants submitted to a radicular pruning at 1/3 and 2/3 present a better thickening and become woody plants; • The plants submitted to a radicular pruning at 1/3 present higher size of aerial parts; • The plants submitted to a radicular pruning at 2/3 present higher rate of secondary roots. K.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Nursery; Plants; Quercus suber; radicular pruning

Efeitos da poda radicular na produçáo de plantas de sobreiro em viveiro (quercus suber l.) - Santos, Maria de Lourdes; PAULINO, ISABEL MARGARIDA ORFÁO (II Congreso Forestal Español, 1997)
The work was accomplished in the Seed Laboratory of National Forestry Station. The aim is to observe, in the nursery plants production, the pruning root effects made at several levels. The seeds provenance are the selected trees. The results permitted to conclude that: • The plants submitted to a radicular pruning at 1/3 and 2/3 present a better thickening and become woody plants; • The plants submitted to a radicular pruning at 1/3 present higher size of aerial parts; • The plants submitted to a radicular pruning at 2/3 present higher rate of secondary roots. K.
Keywords: Nursery; Plants; Quercus suber; radicular pruning

ENSAYO DE TRATAMIENTOS HERBICIDAS EN CULTIVO DE TRES ESPECIES FORESTALES (P. halepensis, P. nigra y Q. ilex) EN VIVERO - CARRASCO MANZANO, I; OCAÑA BUENO, L; PEÑUELAS RUBIRA, J L; DOMÍNGUEZ LERENA, S (II Congreso Forestal Español, 1997)
Weeds are one of the problems which more economic costs originates in forest nurseries due to their effect on crop growth. In spite of this, the effect of weeds on forest seedlings and their control in the nursery have not been much studied. In this study we have analysed the ability of five herbicides (Pendimethalin, Propizamide, Napropamide, Oxyflurofen and Simazine) in controlling weeds and their possible harmful effect on two Pinus species (Pinus halepensis, P. nigra ) and Quercus ilex in the nursery. Pendimethalin and Propizamide damaged seriously all tree species while Napropamide and Oxyflourfen did not produce any harmful effect and did not control effectively weeds. Simazine controlled weeds not affecting tree seedlings although it had to be applied periodically to mantain its effect on weeds.
Keywords: Herbicides; Nursery

ENSAYO DE TRATAMIENTOS HERBICIDAS EN CULTIVO DE TRES ESPECIES FORESTALES (P. halepensis, P. nigra y Q. ilex) EN VIVERO - CARRASCO MANZANO, I.; OCAÑA BUENO, L.; PEÑUELAS RUBIRA, J. L.; DOMINGUEZ LERENA, S. (II Congreso Forestal Español, 1997)
Weeds are one of the problems which more economic costs originates in forest nurseries due to their effect on crop growth. In spite of this, the effect of weeds on forest seedlings and their control in the nursery have not been much studied. In this study we have analysed the ability of five herbicides (Pendimethalin, Propizamide, Napropamide, Oxyflurofen and Simazine) in controlling weeds and their possible harmful effect on two Pinus species (Pinus halepensis, P. nigra ) and Quercus ilex in the nursery. Pendimethalin and Propizamide damaged seriously all tree species while Napropamide and Oxyflourfen did not produce any harmful effect and did not control effectively weeds. Simazine controlled weeds not affecting tree seedlings although it had to be applied periodically to mantain its effect on weeds.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Herbicides; Nursery

Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L; RAPP ARRARÁS, I (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
Keywords: Containers; Holm oak; Nursery; Plant production

Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L.; RAPP ARRARÁS, I. (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español issue: 57 pub-location: Pamplona
Keywords: Containers; Holm oak; Nursery; Plant production

Estudio de la influencia de distintos sustratos de cultivo en el crecimiento y desarrollo en vivero de plantas de ilex l., Q. SUBER L., P. PINA S TER AIT. y P. HALEPENSIS MILL. - Zazo Muncharaz, J; FRANCISCO CASADO, Ma S; TALLÓN MEDRANO, F (II Congreso Forestal Español, 1997)
The influence on various attributes and morphological and anatomical characteristics of seedlings of the mentioned species, of different formulations of growing media commonly used in nurseries, that have fertilized peat as base component and different percentages of pedite, vermiculite, pine bark and sand as ancillary or aeration components, and using the same container, is studied. The obtained results can be applied to propose growing media and cultivation techniques for production of morphological and anatomical quality plants of the mentioned species.
Keywords: Growing medium; Nursery; Plant quality